2017
DOI: 10.1108/bfj-07-2016-0344
|View full text |Cite
|
Sign up to set email alerts
|

Dual pillars of hotel restaurant food quality satisfaction and brand loyalty

Abstract: Purpose The purpose of this paper is to investigate the impact of service quality (physical quality and staff behaviour) and brand equity (brand quality, brand awareness and brand image) on hotel restaurant food quality satisfaction and brand loyalty among international and local travellers in Malaysia. Design/methodology/approach A total of 354 valid questionnaires were collected to assess the measurement and structural model for reflective latent constructs using the two steps of covariance-based structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 54 publications
(85 reference statements)
0
24
1
Order By: Relevance
“…Summarizing Model 1, four causal relationships had positive and significant effects, as indicated in the scientific literature [6,16,17,27,37,[41][42][43][45][46][47][48][49][50][51][54][55][56]58]. A negative causal relationship was obtained between satisfaction and eWOM, with a lower-than-expected level of importance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Summarizing Model 1, four causal relationships had positive and significant effects, as indicated in the scientific literature [6,16,17,27,37,[41][42][43][45][46][47][48][49][50][51][54][55][56]58]. A negative causal relationship was obtained between satisfaction and eWOM, with a lower-than-expected level of importance.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between service quality and consumer satisfaction has been quite extensively studied (e.g., [27,[41][42][43][44]), but at present, the fulfillment of technical requirements is not good enough, and consumers already expect something else, mainly to surprise them. This forces the research field to move from the most technical elements to the most psychological and emotional aspects of the tourist service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the studies that analyse the guests' cultural differences are mainly based on primary data and statistical methods such as factor analysis (Chen and Tsai 2019;Kozak 2001;Pizam and Reichel 1996;Pizam and Sussmann 1995;Selma Ozdipciner et al 2012), t-tests (Chen and Tsai 2019;Pizam and Sussmann 1995;Schuckert et al 2015), analysis of variance (ANOVA) (Chen and Tsai 2019;Emir 2013;Pizam and Sussmann 1995;Selma Ozdipciner et al 2012), and structural equation model (SEMs) (Bihamta et al 2017;Chun et al 2018;Reisinger and Turner 2003;Turner et al 2002). Additionally, as we will analyse below, hotel guests' satisfaction has also been studied through hybrid multicriteria decision-making mathematical methods in which Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) have been applied jointly with fuzzy logic or machine learning (Martín et al 2018;Nilashi et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, brand loyalty, perceived quality, brand awareness, brand associations were identified in the study of 12 brands in three product categories (athletic shoes, film for cameras, and color television sets) [34]; six brands in two product categories (cars and televisions) [35]; and brands available in the Chinese sportswear category [5]. BE was also analyzed in relation to the hospitality industry as hotel BE [36][37][38][39][40][41][42][43][44], the catering industry as restaurant BE [43,[45][46][47], and the airline industry as airline BE [48][49][50]. The following elements were identified in the hotel BE research: brand loyalty [38,40,43,[51][52][53], brand awareness [38,40,42,52,54], brand associations [54], perceived quality [38,40,43,[51][52][53], brand image [38,40,42,43,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Specific elements of the BE were also pointed out, i.e., corporate social responsibility [55], brand satisfaction [56], physical quality [42], staff behavior [42], as well as information and communication technology [57]. Research on restaurant services identified the following elements of restaurant BE: brand awareness [45][46][47]58], brand image [46,58], brand loyalty [47,58], brand association [45,47], quality expressed as brand quality [46], perceived quality [47,58], as well as food and service quality [45]. Brand trust, brand reputation [45], and green activities were also pointed as elements of restaurant BE [59].…”
Section: Introductionmentioning
confidence: 99%